A year in the life of the streptococcus. (4th April 2011) - Mosley, E T; McMahon, A M; Shackley, F; Wairuru, C
Abstract : Introduction: Mild streptococcal infections infection are extremely common, however invasive infections can lead to high mortality. Described in 1982, post streptococcal reactive arthritis (PSRA) has been reported with increasing frequency. Aim: We aimed to look at the number of children presenting to a Tertiary Children's Hospital, with serological significant streptococcal illnesses, diagnoses and antibiotic treatment of those patients. We aimed to identify the patient population with possible Rheumatological conditions, and those who were seen in Rheumatology clinic. Method: We looked at the number of patients where Antistreptolysin O test (ASOT) were performed. Results > 400 were reviewed. Patient case notes were reviewed for diagnosis, antibiotics prescribed and duration of treatment. Results: Department & Number of patients seen in 2009 Emergency Department 46 700 GP referral unit 4861 General medical clinic new referrals 9776 General medical clinic follow-up 39 915 Rheumatology clinic new referral 19 Rheumatology clinic follow-up 338 ASOT's ASOT's January 2009–December 2010=645 N patients=359 N ASOT's >400=100 (28%) Notes reviewed=95/100 patients Diagnoses & Number of patients Urticaria 11 Tonsillitis 9 Pneumonia/empyema 8 Lymphadenopathy 8 Rheumatological (2 SoJIA, 3 JIA, 2 PSRA, 1 irritable hip) 8 Nephritis/haematuria 7 Dermatology other 7 Recurrent streptococcal illness 5 Vasculitis (HSP 4 Wegeners 1) 5 Asthma/WAVE 4 Chronic Fatigue 3 Meningitis/encephalitis 3 Kawasaki 2 Immunological (PFAFA, Autoimmune) 2 Neurological 2 Fever Unspecified 2 Gastroenterology 2 EBV 2 TB 2 UTI 1 Endocarditis 1 Osteomyelitis 1 N° patients with conditions commonly seen in Rheumatology clinics (Bold above )=25 N° patients seen in the Rheumatology clinic=12 Antibiotics 65/95 were prescribed antibiotics. Length of Antibiotic & Number of Patients 48hrs 1 Up to7 days 15 8–14 days 37 2 weeks–6 weeks 4 >6 weeks 8 Conclusions: Less than 1/3 of those patients in whom ASOT's were performed were significantly raised. 1/4 of patients with positive streptococcal serology had a rheumatological diagnosis, suggesting it is a significant trigger in rheumatological conditions. Learning points: ▶ Need for education on rational antibiotic policies, allowing appropriate treatment for streptococcal eradication. ▶ Possible need for streptococcal screening in rheumatological patients ▶ Paediatricians should consider rheumatological conditions in patients with positive results.